Decision Support Model for User Submission Approval Energy Partners Candidate Using Profile Matching Method and Analytical Hierarchy Process - Moedjiono Moedjiono; Nia Rahma Kurnianda; Aries Kusdaryono (Scientific Journal of Informatics)
In the field of services, customer satisfaction is a very important factor and determine the success of an enterprise. In the field of outsourcing, customer satisfaction indicator is the labor required delivery in a timely manner and has a level of quality in accordance with the terms proposed by the customer. To provide the best talent to customers, team recruitment and selection must perform a series of tests with a variety of methods to match the criteria of office given by the user with the criteria owned candidates and in order to support growth in graduation rates force a partner at the stage of user approval. For this purpose, the authors conducted a study with the method of observation, interviews, document reviews the candidate recruitment process, so as to provide recommendations for candidates with the highest quality delivery to the user at the stage of approval. The author put forward a model of decision support that is supported by the method of profile matching and Analytical Hierarchy Process (AHP) in problem solving. The final results of this study can be used to support a decision in order to improve the effectiveness of the delivery of quality candidates, increase customer satisfaction, lower costs and improve gross operational margin of the company.